Left septal fascicular block : characterization, differential diagnosis and clinical significance /: characterization, differential diagnosis and clinical significance. (2016) - Pérez-Riera, Andrés R; Barbosa-Barros, Raimundo; Baranchuk, Adrian
No abstract available